Indonesian Women in Kamus Besar Bahasa Indonesia (KBBI) (1988–2018): A Lexicographic Corpus: A Corpus Lexicography - Febrina, Ria; Suhandano; Sutrisno, Adi (Jurnal Arbitrer, 2024)
Indonesian women have undergone significant changes over time, as reflected in the vocabulary of the Kamus Besar Bahasa Indonesia (KBBI). This study aims to describe the representation of Indonesian women in the KBBI and to explain the development of their social and cultural lives over 30 years (1988–2018). The research employs a descriptive-qualitative approach by collecting data through the extraction of entries, definitions, compound words, and proverbs containing the terms “perempuan” (woman) and “wanita” (lady) from two printed editions of the KBBI: the first edition (1988) and the fifth edition (2018). Data analysis was conducted using Sketch Engine to analyze 1,381,578 tokens, and the findings revealed 1,148 collocations and concordances related to the terms “perempuan” and “wanita.” The results indicate that the study of Indonesian women within a linguistic corpus offers insights into their contributions over 30 years across various fields such as religion, military, economy, journalism, health, politics, arts and culture, and beauty. Through corpus-lexicography studies, the portrayal of Indonesian women in the dictionary has challenged patriarchal views that traditionally positioned women as inferior to men. This research highlights the importance of recognizing the representation of women in the social dynamics of Indonesian society. It offers a significant contribution to the broader field of Indonesia lexicography studies by examining how women are represented in dictionary entries.